PENTINGNYA PEMBUKUAN DALAM PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) - Amin, Asbi; Azizah Basmar, Nur; Anwar, Anwar; Nuramal, Nuramal; Sahidah, Sahidah (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
This Community Service activity is carried out with the aim that the managers of Patallassang Village-Owned Enterprises (BUMDes) of Pangkep Regency can know the importance of doing bookkeeping correctly for the transactions of each business. Good simple bookkeeping can be used as one of the activity analysis tools and developed for other interests that are more useful for the development of BUMDes. The method used in this PKM activity is lecture / socialization with the delivery of material from resource persons regarding simple bookkeeping. Simple bookkeeping training is carried out well, with the training, participants are expected to be able to apply simple bookkeeping knowledge.